Clinical and Cost-Saving Effects of the Drug Utilization Review Modernization Project in Inpatient and Outpatient Settings in Korea. Issue 6 (19th September 2022) - Yoon, Dongwon; Song, Inmyung; Jeon, Ha-Lim; Bea, Sungho; Choi, Ahhyung; Lee, Hyesung; Shin, Ju-Young
Abstract : Objectives: Korea's national health insurance authority introduced a drug utilization review modernization pilot project in which health professionals provided follow-up services to monitor adverse drug events. We aimed to evaluate the effects of the project on clinical and economic outcomes. Methods: We conducted difference-in-differences analysis using National Health Insurance claims data from the Health Insurance Review and Assessment Service. We calculated the number of adverse drug events and allergic reactions as a clinical indicator and medical costs incurred to manage these events as an economic indicator. Absolute difference in each outcome measure was defined as the value after the project minus the value before the project. Difference-in-differences was defined as a difference in absolute differences between the intervention group and the control group. Results: Overall, difference-in-differences were −43 and −826 for the number of drug-related adverse events and allergic reactions and −198, 700 and 53, 318 for medical costs in the inpatient and outpatient settings, respectively. For outpatients, the monthly number of adverse drug events and allergic reactions has grown higher for the control group than for the intervention group after implementation of the pilot project. Conclusions: Implementation of the pilot project lowered the number of adverse drug events and allergic reactions in the inpatient and outpatient setting. The project also lowered medical costs incurred to manage these events in the inpatient setting only. Based on our findings, we recommend that the pilot project be expanded on a nationwide level at least in the inpatient setting.